Additional impact of mutational genotype on prognostic determination in resistant and relapsed acute myeloid leukaemia. (September 2021) - Linch, David C.; Hills, Robert K.; Gilkes, Amanda; Burnett, Alan K.; Russell, Nigel; Gale, Rosemary E.
Highlights: Outcome differs in younger adult AML patients with resistant and relapsed disease. Mutational genotype adds additional prognostic information in the two subgroups. In resistant disease, NPM1 Mutant was associated with better remission and survival. NPM1 mutant was more beneficial in relapsed patients who had not received an allograft. Abstract: Outcome after failure of initial therapy in younger adult patients with acute myeloid leukaemia (AML) is highly variable. Cytogenetics, length of first remission (CR1) before relapse, and allogeneic transplantation are known prognostic factors, but the contribution of leukaemic genotype is less clear, particularly in resistant disease. Of 5, 651 younger adult patients entered into UK MRC/NCRI AML trials between 1988 and 2014 with available FLT3 ITD and NPM1 genotype, 326 (6%) had resistant disease and 2338 (41 %) relapsed after achieving CR1. Overall survival (OS) was significantly higher in relapsed compared to resistant disease (p = 0·03). Independent favourable prognostic factors for OS in resistant disease included lower blast cell percentage after two courses of induction therapy (p = 0.0006) and NPM1 mutant ( NPM1 MUT ) (p = 0.04). In relapsed disease, longer CR1 was a favourable independent factor for attainment of CR2 (p < 0.0001) and OS from time of relapse (p < 0.0001), but CR2 rate and OS from relapse were significantly worse in those who had received an allograft in CR1 (respectively p < 0.05, p < 0·002). NPM1 MUT was marginally beneficial for OS (p = 0.04). FLT3 ITD and DNMT3A MUT were adverse factors for OS (respectively p < 0.0001, p = 0.02). Mutational analysis adds additional independent prognostic information to demographic features and previous therapy in patients with resistant and relapsed disease.